Clinical significance of Q waves in ischemic cardiomyopathy. (8th February 2021) - Rodenas Alesina, E; Jordan, P; Herrador, L; Espinet-Coll, C; Pizzi, N; Aguade-Bruix, S; Ferreira-Gonzalez, I
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): CIBER-CV AIMS: The scintigraphic translation of Q waves in patients with ischemic cardiomyopathy and LVEF < 40% has not yet been assessed. The aim of this study was to explore the relationship between Q waves and necrotic tissue and to analyze their impact in prognosis. METHODS AND RESULTS: A retrospective study enrolling 487 consecutive patients (67, 0 [57, 4 – 75, 4] years), with ischemic cardiomyopathy, LVEF <40% and narrow QRS who underwent stress-rest SPECT was conducted. Patients with Q waves (320 patients [65, 7%]) had less comorbidity and ischemia, but more necrosis. Q waves correlated poorly with lack of viability (AUC = 0, 63) and were independently associated with the subendocardial extent of the necrosis. After a follow-up of 5, 07 years, the primary outcome (cardiovascular death, heart failure hospitalization or myocardial infarction) occurred in 192 (39, 4%) patients, without differences between groups in multivariate analysis. After accounting for non-cardiovascular death as a competitive risk, the interaction between >10% of ischemia and revascularization remained in Cox model both in the total cohort (aHR= 0, 46 [0, 24 – 0, 86]), and in patients with Q waves (aHR = 0, 27 [0, 11–0, 69]). CONCLUSION: Patients with ischemic cardiomyopathy with Q waves have larger subendocardial scarring and more transmural necrosis, although correlation between Q waves and transmural scarring is poor. Revascularization if >10% ischemia is present is associated with a better prognosis. Ischemia burden should be assessed and accordingly treated in these patients, and no differences in management should be made in the presence of Q waves.